STRATEGI INOVASI DALAM PENGEMBANGAN SDM: MEMBUKA POTENSI KREATIF DAN KOLABORATIF(Kementerian Keuangan Republik Indonesia) - Ali Mahadi Ritonga; Ahmad Sabili Yuhda, Angga Pradana Kusuma, Nanda Kurniawan Lubis, Suhairi (CV. ADIBA AISHA AMIRA, 2023)
In today's digital era, it gives birth to technological innovations that change a lot of the way of working and living and in doing work. Technological updates that occur give birth to various opportunities in all sectors of human life. However, the progress that occurs can take over the work done by humans. So the need for mature readiness in building quality human resources to balance existing technological advances. This research was conducted to find out how strategies can be carried out in efforts to develop human resources in the current era. The purpose of this study itself is to explain, analyze, and examine how strategies in building human resources in facing the current digital era. The type of method carried out in this study is a literature method with a descriptive analysis approach